2010
DOI: 10.3109/02713680903447926
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Photopic Negative Response of Focal Electroretinograms and Local Loss of Retinal Neurons in Glaucoma

Abstract: These results strongly suggest that the anatomical losses of retinal neurons in local areas of the retina or optic nerve head are a cause of the reduction in the amplitude of the focal photopic negative response in open angle glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…However, within the perimetric patient group, a direct correlation between the two was absent. Consistent with previous studies, the RNFLT was significantly reduced in pre-perimetric and perimetric patients [4,39,40]. Furthermore, the significant correlation between the LN-off and LN-add amplitudes and the RNFLT indicates that LN-off component is a more sensitive indicator for retinal nerve fibre layer integrity than the LN-on component.…”
Section: Correlation Between Lns and Other Functional And Structural supporting
confidence: 90%
See 1 more Smart Citation
“…However, within the perimetric patient group, a direct correlation between the two was absent. Consistent with previous studies, the RNFLT was significantly reduced in pre-perimetric and perimetric patients [4,39,40]. Furthermore, the significant correlation between the LN-off and LN-add amplitudes and the RNFLT indicates that LN-off component is a more sensitive indicator for retinal nerve fibre layer integrity than the LN-on component.…”
Section: Correlation Between Lns and Other Functional And Structural supporting
confidence: 90%
“…Recent data have shown that the PhNR is correlated with functional measures of retinal ganglion cells integrity like visual field [5,35] and with structural parameters like retinal nerve fibre layer thickness (RNFLT) in glaucoma patients [4,39,40] and in patients with optic nerve atrophy [37]. Similarly, there is evidence that PERG amplitudes are correlated with visual field defects [41] and the RNFLT in glaucoma patients [42].…”
Section: Introductionmentioning
confidence: 93%
“…The PhNR amplitude was measured from the baseline to the negative trough at 70 msec according to the findings in earlier studies [18,19]. The amplitudes of OP1, OP2, and OP3 were measured and summed, and are designated as ÎŁOPs as reported [18,20].…”
Section: Focal Macular Erg (Fmerg) Recordingsmentioning
confidence: 99%
“…22 To reduce variability among individuals, the amplitude of the PhNR was normalized by that of the b-wave and this ratio was designated as the PhNR/b-wave amplitude ratio. [23][24][25][26] The ERG recordings were made 12 months after MH surgery for the MH patients.…”
Section: Recording Focal Macular Electroretinogramsmentioning
confidence: 99%
“…[22][23][24][25][26] We have found that the amplitude of the focal PhNR was correlated with a decrease in retinal sensitivity 23 and retinal neurons represented by rim area of the optic disc and nerve fiber layer thickness. 26 Thus, the focal PhNR amplitude is related to the severity of the OAG.…”
Section: Introductionmentioning
confidence: 99%